Autoimmune hepatitis – primary biliary cirrhosis and overlap syndrome: A case report - kumbhar, Deepak; Satarker, Vrishab; Sawant Dessai , Bhargav (Indian Journal of Case Reports, 2024)
Important immune-mediated liver illnesses include autoimmunity hepatitis (AIH) and primary biliary cirrhosis. Typically, they are distinguished based on histological, biochemical, serological, and clinical parameters. Diagnostic criteria for many conditions are typically met by patients with autoimmune liver disease. The diagnosis of AIH/primary sclerosing cholangitis overlap is based on a mix of biochemistry, autoantibody profile, cholangiogram, and liver histology; there are no universally accepted criteria for this. The patient can remain asymptomatic or present with pruritis and jaundice. Diagnosis is through liver biopsy showing bile duct destruction and proliferation. The treatment is by high-dose ursodeoxycholic acid.